Floor space requirement for housing and welfare of pigs under Indian perspective - PATEL, B H M; KASWAN, SANDEEP (The Indian Journal of Animal Sciences, 2019)
Pork production in India has almost doubled from 0.204 MT to 0.402 MT in last decade (2007–08 to 2017–18). Best utilization of pen space without adversely affecting the productivity and well-being of pigs is crucial for pork sector. Most of the developed countries recommend floor space requirement of 0.15 m2/pig for weaners and South Asian countries as 0.3 to 0.5 m2/pig without any provision of open space. In India, very few studies have been carried out on space allowance in pigs. Since, Indian Standards (IS: 3916–1966) for pig housing are very old (1960s), study on the floor space requirement for individual pig in all the stages and different group sizes is very much essential for practical pig rearing. The negative impact of crowding on feed intake and growth is well documented. Higher stocking density may also adversely affect feed conversion efficiency. However, reduction in floor area (33% and 50%) in comparison to IS did not affect major performance traits. Space allowance is one of the important factors in the establishment of social rank. In European countries, the most economical allocation of pen floor space was less than the space needed for optimal performance. Reduced space allowances may lead to amplified aggression-related skin lesion scores. Thus, in space restricted environments, the dominance hierarchy becomes less stable amongst pigs and tail and ear biting are also commonly observed. Based on studies done so far it is concluded that there is scope of reduction in floor space allowance in comparison to IS specifications without compromising welfare status of pigs and further research in this area need to be encouraged.